2012
DOI: 10.1143/jjap.51.11pe06
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Tungsten Oxide Nanowires Compared to Bulk Particles

Abstract: The electrochemical properties of oxygen-deficient tungsten oxide (W 18 O 49 ) nanowires were investigated. The nanowires were prepared via a simple thermal evaporation method. The as-deposited nanowires were 60-90 nm in diameter and several micrometers long as measured by fieldemission scanning electron microscopy. The crystal structure was indexed to the monoclinic W 18 O 49 phase. The electrochemical properties of the nanowires and WO 3 bulk particles were examined by cyclic voltammetry between 2 and 4 V vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
(44 reference statements)
1
5
1
Order By: Relevance
“…The peak of 21º came from CMC 25 . 10 The open circuit voltage of these cells laid at about 3.1 V. During the first insertion process, an obvious discharge curve profile was observed for W 18 15 There were three discharge voltage plateaus (1.5, 0.6 and 0.3 V) and two charge voltage plateaus (1.1 and 1.6 V) observed in the initial discharge and charge process, which agreed well with its CV curve profile. After charge, the diffraction peaks could 10 be indexed to W 18 15 electrodes was recorded between 0.01 V and 3.0 V, as is shown in Fig.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…The peak of 21º came from CMC 25 . 10 The open circuit voltage of these cells laid at about 3.1 V. During the first insertion process, an obvious discharge curve profile was observed for W 18 15 There were three discharge voltage plateaus (1.5, 0.6 and 0.3 V) and two charge voltage plateaus (1.1 and 1.6 V) observed in the initial discharge and charge process, which agreed well with its CV curve profile. After charge, the diffraction peaks could 10 be indexed to W 18 15 electrodes was recorded between 0.01 V and 3.0 V, as is shown in Fig.…”
Section: Resultssupporting
confidence: 72%
“…2(g-i) showed that similar nanowire bundles with a thin carbon layer of about 0.6 nm thickness was observed for W 18 O 49 /C-2. After charge, the diffraction peaks could 10 be indexed to W 18 15 electrodes was recorded between 0.01 V and 3.0 V, as is shown in Fig. 2(j-l) showed that the aggregation of nanowire bundles was observed for W 18 85 In order to investigate the electrochemical reaction mechanism, bare W 18 O 49 and W 18 O 49 /C-1 anodes were characterized by XRD after charge and discharge.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…1,2) WO 3 with a distorted ReO 3 -type structure can be regarded as an A-site deficient perovskite, being capable of a host material for intercalations of alkaline and alkaline-earth metals. [3][4][5][6][7] Smaller H and Li atoms are easily intercalated to the amorphous or polycrystalline films, and the resultant doping electrons color WO 3 . Because coloration of A x WO 3 is attributed to increasing number of electrons in the W 5d states, it will be associated with an electronic phase transition such as insulator to metal transition (IMT).…”
mentioning
confidence: 99%